Sosialisasi Pemilih Pemula untuk Pemilihan yang Bermakna di SMA Negeri 3 Takalar - Dyan Paramitha Darmayanti; Darman Manda; Kurnia Ali Syarif; Yusi Irensi Seppa; Ibrahim Arifin (Panrita Inovasi: Jurnal Pengabdian Kepada Masyarakat, 2024)
This activity aims to introduce beginner voters at SMA Negeri 3 Takalar to the importance of participating in the 2024 Presidential Election. The socialisation material included an explanation of the Indonesian political system, the importance of participating in elections, and the impact of political decisions. Resource persons were invited to provide students with an in-depth understanding of these political issues. The socialisation was conducted in an interactive manner, including question and answer sessions and discussions, to increase participants' understanding and engagement. The impact of this activity includes increased understanding and awareness of participants, especially SMA Negeri 3 Takalar students, about the importance of their voting rights in a democracy. In addition, this activity also succeeded in encouraging students' active participation in the political process by motivating them to take part in the 2024 Presidential Election and realising the influence of their votes on the political direction and policies of the country. Although there were some obstacles such as time and resource constraints, as well as the lack of motivation of participants in certain cases, careful planning efforts succeeded in overcoming these obstacles. Good cooperation between the service team and the school (SMA Negeri 3 Takalar) is the key to the success of this activity. Therefore, this service makes a positive contribution in preparing the younger generation to play an active role in the world of Indonesian politics and democracy. It is hoped that increasing political understanding among students will bring positive benefits in forming a smart, critical and responsible society.